2017
DOI: 10.1038/s41598-017-08926-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal acclimation mitigates cold-induced paracellular leak from the Drosophila gut

Abstract: Chill susceptible insects suffer tissue damage and die at low temperatures. The mechanisms that cause chilling injury are not well understood but a growing body of evidence suggests that a cold-induced loss of ion and water homeostasis leads to hemolymph hyperkalemia that depolarizes cells, leading to cell death. The apparent root of this cascade is the net leak of osmolytes down their concentration gradients in the cold. Many insects, however, are capable of adjusting their thermal physiology, and cold-acclim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 67 publications
(79 reference statements)
6
58
2
Order By: Relevance
“…Similar to trends observed in Drosophila , we predicted that a large and rapid increase in gut FITC-dextran concentration (i.e. serosal to mucosal leak) would occur over time in the cold (MacMillan et al, 2017). However, when each gut segment was analysed for marker content, we found that cold stress induced minimal leak from the hemolymph into the gut (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Similar to trends observed in Drosophila , we predicted that a large and rapid increase in gut FITC-dextran concentration (i.e. serosal to mucosal leak) would occur over time in the cold (MacMillan et al, 2017). However, when each gut segment was analysed for marker content, we found that cold stress induced minimal leak from the hemolymph into the gut (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…To measure paracellular permeability in the gut epithelia of locusts, we monitored the movement of a fluorescently-labeled molecule in both the serosal (hemolymph) to mucosal (lumen) direction, and the mucosal to serosal direction. All experiments used FITC-dextran (3-5kDa, Sigma Aldrich, St. Louis, USA) a commonly used probe for determining paracellular permeability in both invertebrate and vertebrate models such as fruit flies ( D. melanogaster ), rats ( Rattus norvegicus domesticus ), and zebra fish ( Danio rerio ) (see MacMillan et al, 2017; Condette et al, 2014; Bagnat et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jonusaite, Kelly, & Donini, 2017). In D. melanogaster male reproductive behaviors are negatively influenced by severe cold exposure (Singh & Prasad, 2016), but exposure to brief cold acclimation (i.e., rapid cold hardening) preserves male reproductive behavior and success (Shreve et al, 2004).…”
Section: Discussionmentioning
confidence: 99%